Seed maturation and effect of temperature regime on Trema micrantha (L.) Blume seed germination - Castellani, E. D.; Aguiar, I. B. (My University, 2001)
T. micrantha (L.) Blume (Ulmaceae), a common pioneer tree species in Brazil, is used in the restoration of degraded areas. The fruits are fleshy and indehiscent, with only one water impermeable seed. During the fruiting period, fruits of different colours are found at the same time on the same branch. This research aimed to correlate fruit colour with other physical indicators of seed maturity and to verify the effect of temperature regime on seed germination. Collected fruits were separated in to green, green-red and red colour and for each of these maturation stages, size, moisture content and dry matter of both fruits and seeds were determined. Seeds were scarified with sulphuric acid and submitted to a germination test conducted at constant (20°C, 30°C and 40°C) and alternating (20-30°C, 30-40°C and 20-40°C) temperatures for 15 weeks. Seed germination percentage and speed were analysed after five weeks and the final percentage of germinated and viable seeds after 15 weeks. Seed maturity is attained when the fruits are green-red. At this stage, moisture content was about 64% for fruits and 10% for seeds. Alternating temperature was required for seed germination and 20-30°C was the best option. Most seeds had germinated after five weeks, providing mature seeds, acid scarification and alternating temperature were used.